GME versus OLS - Which is the best to estimate utility functions? - Pires, Cesaltina (2010)
This paper estimates von Neumann and Morgenstern utility functions comparing the generalized maximum entropy (GME) with OLS, using data obtained by utility elici-tation methods. Thus, it provides a comparison of the performance of the two esti-mators in a real data small sample setup. The results confirm the ones obtained for small samples through Monte Carlo simulations. Overall the results suggest that GME is an interesting alternative to OLS in the estimation of utility functions when data is generated by utility elicitation methods.